Influence of the COL5A1 rs12722 on musculoskeletal injuries in professional soccer players - Massidda, M.; Bachis, V.; Corrias, L.; Piras, F.; Scorcu, M.; Calò, C. M. (The Journal of Sports Medicine and Physical Fitness, 2016)
AIM: The aim of this study was to investigate whether COL5A1 rs12722 polymorphism is associated with musculoskeletal injuries in elite soccer players.